Občanska znanost v 5 korakih: Načrtovanje in oblikovanje projektov - Kunaver, Uroš; Muršič, Zarja; Amalia Robinson, Johanna; Romih, Tea (University of Maribor Press, 2025)
Citizen Science in 5 Steps: Planning and Designing Projects. Citizen Science in 5 Steps: Planning and Designing Projects comprehensively presents the concept of citizen science, which is not only a method of collecting scientific data with the help of non-professional researchers, but also a way of connecting scientific research with communities and individuals who actively participate in solving current research problems, thereby democratizing science. The publication takes readers (researchers as well as high school and university students, members of various associations, representatives of different social groups, amateur researchers, and the wider interested public) through the history and terminology of citizen science, and then explains five key steps in planning and designing citizen science projects: from defining the research problem, designing a plan, and building a community of participants, to creating and analyzing data and sharing results. The handbook can be read from cover to cover or it can be used as a guide for a specific step in the planning and design of a citizen science project.